Is nitric oxide involved in the antinociceptive activity of tramadol? Findings in a rat model of neuropathic pain - Okuducu, Hasan; Onal, Selami Ates (Kare Publ, 2005)
The aim of this investigation was to assess the role that NO plays in the antinociceptive activity of tramadol using a rat model of neuropathic pain. Thirty male Wistar rats weighing 200-250 g were randomly divided into five equal groups. The neuropathic pain model used for the study was chronic constrictive injury (CCI) model. Three weeks after the surgical procedure, each rat was tested to assess mechanical threshold in grams using an electronic algometer. After CCI was induced, tramadol hydrochloride was administered by intraperitoneal (i. p.) injection in all groups, and N(omega) nitro -L -arginine (L-NA) and L-arginine were administered i. p. or intrathecally (i. t.) depending on the group. Tramadol was administered in 10 mg/kg doses i. p., L-NA was given in 10 mg/kg doses i. p. and in 30 mu g/kg doses i. t.. L-arginine was given in 10 mg/kg doses i. p. and in 50 mu g/kg doses i. t.. The multiple agents were given 30 minutes apart from cach administration. Intraperitoneal administration of tramadol (Group 1) only increased mechanical threshold in the rats' left hind paw, whereas in i. p. L-NA group (10 mg/kg) (Group 2) produced a significant reduction of the mean mechanical antinociceptive threshold (p< 0.05). Like this, in i. t. L-NA group (30 mu g/kg) (Group 4) a significant reduction of the mean mechanical antinociceptive threshold (p < 0.05) was also observed. The mean threshold values in Group 2 (i. p. tramadol + i. p. L-NA) and Group 4 (i. p. tramadol + i. t. L-NA) were not significantly different. The mean threshold values in Groups 3 (i. p. tramadol + i. p. L-NA + i. p. L-arginine) and 5 (i. p. tramadol + i. t. L-NA + i. t. L-arginine) were also similar. The mean mechanical antinociceptive threshold was significantly increased in Group 3 (i. p. L-NA + L-arginine) and Group 5 (i. t. L-NA + L-arginine) when compared to Group 1 (i. p. tramadol only) (p< 0.05 for both). The results of this study support the involvement of the L-arginine/nitric oxide pathway in the antinociceptive effect of tramadol in a rat model of neuropathic pain.
Keywords: Chronic constriction nerve injury; tramadol; nitric oxide; N(omega) - nitro - L - arginine; L-arginine; antinociception